2021
DOI: 10.24815/siele.v8i1.18110
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian EFL university students' metacognitive online reading strategies before and during the Covid-19 pandemic

Abstract: This descriptive study focused on investigating the use of metacognitive online reading strategies that were associated with learning conditions before and during the Covid-19 Pandemic. The respondents were 244 Indonesian EFL students taking an English subject at the Borneo Tarakan University. Data were collected using the Online Survey of Reading Strategies (OSORS) through the application of Google Form. The collected data were analyzed descriptively and quantitatively. The results showed that before the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The two other questionnaires, SORS and OSORS, are based on the conception of classifying reading strategies into global reading strategies, problem-solving strategies, and support strategies. The findings of the reviewed studies, in general, show that the most frequently used reading strategies were problem-solving strategies, which is followed by global reading strategies, and finally support strategies (Meniado, 2016;Omar, 2014' Yaghi, 2021, Behdani, Sharif & Hemmati, 2016Pasaribu, 2017;Ahmadian & Pasand, 2017;Mukhli & Amir, 2017;Rianto, 2021). However, one of the studies (Al-Seghayer.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The two other questionnaires, SORS and OSORS, are based on the conception of classifying reading strategies into global reading strategies, problem-solving strategies, and support strategies. The findings of the reviewed studies, in general, show that the most frequently used reading strategies were problem-solving strategies, which is followed by global reading strategies, and finally support strategies (Meniado, 2016;Omar, 2014' Yaghi, 2021, Behdani, Sharif & Hemmati, 2016Pasaribu, 2017;Ahmadian & Pasand, 2017;Mukhli & Amir, 2017;Rianto, 2021). However, one of the studies (Al-Seghayer.…”
Section: Resultsmentioning
confidence: 96%
“…All of them include a focus on self-reported strategy use through Reading Strategy Use Questionnaire (Naseri & Zaferanieh, 2012), Survey of Online Reading Strategies (SORS) (Meniado, 2016;Pei, 2014;Al-Seghayer. 2014;Yaghi, 2021, Behdani, Sharif & Hemmati, 2016Pasaribu, 2017;Mukhli & Amir, 2017), Online Survey of Reading Strategies (OSORS) (Omar, 2014;Chen, 2015, Ahmadian & Pasand, 2017Rianto, 2021). A study (Taki & Soleimani, 2012) even used SORS and OSORS.…”
Section: Resultsmentioning
confidence: 99%
“…The sudden closures of schools worldwide due to the Covid-19 pandemic has challenged the face-to-face in-classroom teaching practices that the education sector currently relies on [10]. Many schools closed at the start of the pandemic, and all teaching and learning were immediately moved to an online platform, changing the way teachers and students interact up until now [11], [12]. According to UNESCO, about 195 countries have closed schools in the spring, 2020, and interrupted more than 1.5 billion students worldwide [13].…”
Section: Current Urgency For Online Learningmentioning
confidence: 99%
“…Some studies suggest a positive correlation between the use of metacognitive reading strategies and reading scores (Alıcı & Serdaroğlu, 2016;Memiş & Kandemir, 2019;Memiş & Kandemir, 2019). Studies investigating online metacognitive reading strategies were Arab World English Journal www.awej.org ISSN: 2229-9327 248 similar to those cited in printed materials (Azmuddin, Nor, & Hamat, 2017;Rianto, 2021). It has been reported that students used problem-solving strategies the most, although global reading and support reading strategies were the least used.…”
Section: Introductionmentioning
confidence: 99%